Bio‐Inspired Imprinting Materials for Biomedical Applications. Issue 28 (31st July 2022) - Chen, Hanxu; Guo, Jiahui; Wang, Yu; Dong, Weiliang; Zhao, Yuanjin; Sun, Lingyun
Abstract: Inspired by the recognition mechanism of biological molecules, molecular imprinting techniques (MITs) are imparted with numerous merits like excellent stability, recognition specificity, adsorption properties, and easy synthesis processes, and thus broaden the avenues for convenient fabrication protocol of bio‐inspired molecularly imprinted polymers (MIPs) with desirable functions to satisfy the extensive demands of biomedical applications. Herein, the recent research progress made with respect to bio‐inspired imprinting materials is discussed in this review. First, the underlying mechanism and basic components of a typical molecular imprinting procedure are briefly explored. Then, emphasis is put on the introduction of diverse MITs and novel bio‐inspired imprinting materials. Following these two sections, practical applications of MIPs in the field of biomedical science are focused on. Last but not least, perspectives on the remaining challenges and future development of bio‐inspired imprinting materials are presented. Abstract : Inspired by the recognition mechanism of biological molecules, molecular imprinting techniques are imparted with numerous merits and thus broaden the avenues for convenient fabrication protocol of bio‐inspired molecularly imprinted polymers with desirable functions to satisfy the extensive demands of biomedical applications. Herein, the recent research progress made with respect to bio‐inspired imprinting materials in this review is discussed.